2009
DOI: 10.1080/10705420903299961
|View full text |Cite
|
Sign up to set email alerts
|

Community Gardening and Community Development: Individual, Social and Community Benefits of a Community Conservation Program

Abstract: Community agriculture and conservation initiatives have become increasingly important components of sustainable community development strategies, particularly in disadvantaged neighborhoods. This study examines a community conservation program whose goal was to foster revitalization through the establishment of floral and vegetable gardens primarily in distressed areas. Respondents indicated that the program contributed to revitalizing neighborhoods, as well as their beliefs and behavior regarding conservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 16 publications
1
81
0
4
Order By: Relevance
“…Some AFN projects explicitly aim to serve a particular community conceptualized in this way (Glover, 2003;Saldivar-Tanaka & Krasny, 2004), while others work with nearby residents as a part of their daily operations (Nettle, 2014). For some AFN participants, their engagement with the AFN motivates them to expand their community involvement beyond AFN activism (Armstrong, 2000;Ohmer et al, 2009). Some urban agricultural projects are established explicitly to address broader social issues, such as racial and ethnic inequalities (Morales, 2011;White, 2010), although these projects remain the exception.…”
Section: Afns' Community-building Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Some AFN projects explicitly aim to serve a particular community conceptualized in this way (Glover, 2003;Saldivar-Tanaka & Krasny, 2004), while others work with nearby residents as a part of their daily operations (Nettle, 2014). For some AFN participants, their engagement with the AFN motivates them to expand their community involvement beyond AFN activism (Armstrong, 2000;Ohmer et al, 2009). Some urban agricultural projects are established explicitly to address broader social issues, such as racial and ethnic inequalities (Morales, 2011;White, 2010), although these projects remain the exception.…”
Section: Afns' Community-building Potentialmentioning
confidence: 99%
“…Studies have explored which operational structures of AFNs enhance interactions among the participating individuals (Kurtz, 2001;Macias, 2008) and how a sense of community is experienced by community gardeners, CSA members, or farmers market patrons (Glover, 2004;Ostrom, 2007;Saldivar-Tanaka & Krasny, 2004). Other studies have investigated the extent to which community engagement motivates AFN participants to become socially active (Cox, Holloway, Venn, Dowler, Hein, Kneafsey, & Tuomainen, 2008) or how the social impact of AFN activities may extend beyond gardening or distributing food and enable mobilization toward other social issues faced by the community (Armstrong, 2000;Nettle, 2014;Ohmer, Meadowcroft, Freed, & Lewis, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the aesthetic appeal of gardening emerged as a few participants spoke of how they liked to walk around the neighborhood to look at other peoples' gardens, but more in the context of viewing their flowers and not their vegetables. This is supported by studies that illustrate the importance of gardens as a way to beautify neighborhoods and create a sense of community amongst its residents (Ohmer et al 2009;Milburn and Vail 2010).…”
Section: Gardensmentioning
confidence: 91%
“…Her comments reflect those usually associated with the larger cityscapes and suggest that even the smaller, rural communities, with agricultural and gardening backgrounds, are dealing with issues of 'urbanization'. It also suggests that SP and BV view community gardens as an important component of sustainable community development (Ohmer et al 2009) and as a way to help residents connect with the land and the food that comes from it (Trubek 2008;Milburn and Vail 2010). Community gardens may foster the direct engagement of people with the soil, plants, and the 'fruits' of their labor, while promoting social interaction and community involvement.…”
Section: Gardensmentioning
confidence: 99%
“…In West Hollywood, USA, community garden participants increased their physical activity by 6% and increased their fruit and vegetable consumption by 10% [12]. Ohmer et al [13] found that community gardens improve access to green space in densely urbanised neighbourhoods. Galdini [5] noted that community gardens improve social cohesion and vitality in Berlin.…”
Section: Introductionmentioning
confidence: 99%